Ontolime: modelo de ontologia de descrição de imagens médicas - Santos Neto, Martins Fideles dos [UNESP] (2013)
In the health records of the patients , as well as images linked to them , are a benchmark for access to information and knowledge with emphasis on the treatment of many diseases , and also for research purposes . These records , which before were recorded in analog media ( paper) , currently already being built in electronic media or being scanned , thanks to the integration of electronic and digital technologies of information in the context of health . Another aspect to consider in this area are the images that photographing the body so perfectly making it transparent. In this new paradigm , it is considered that the treatment of these informational documents need to be innovative , and the adoption of ontologies can be a solution . It is therefore in this context that this research fits contemplating the question: what criteria should be used to build a model of the ontology of medical images ? What is the contribution of literature Area Information Science in the process of ontology construction ? The basic objective of this research is to build a model of the ontology of medical images taking into account the images ( human and other animals ) from the terminology of healthcare and information related to images taken from the teaching sites in order to access and information retrieval imagery in health , with higher added value . The research is exploratory in which we seek to deepen our knowledge relative to the understanding of the image in the field of health, informational representation , as well as on ontologies , in general , and particularly ontology pictures . The construction methodology of ONTOLIME , was based on Methontology , prepared by Professors Gomez - Perez and trough (2002 ) . The mapping of concepts has been done manually , terminologies in the area and also in the analysis of images collected on the Internet . The ONTOLIME was built in Protégé software... (Complete abstract click electronic access below)